P100 Intrahepatic and system cytokine profiles in acetaminophen-induced acute liver failure: possible mechanism of immuneparesis. (16th November 2010) - Antoniades, H; Anstee, Q; Bruce, M; Mitry, R; Hussain, M; Auzinger, G; Willars, C; Wayel, J; Concas, D; Heaton, N; Goldin, R; Bernal, W; et al.
Abstract : Introduction: Activation of systemic inflammatory responses in acetaminophen-induced acute liver failure (AALF) is associated with elevated levels of both pro- and anti-inflammatory cytokines. Functional monocyte deactivation has been described and this is thought to contribute to increased susceptibility to sepsis and a higher mortality rate. Anti-inflammatory cytokines play a major part in the resolution of inflammatory responses and promote tissue repair processes but increase the risk of systemic infections. We hypothesise that the levels of anti-inflammatory cytokines mirror the severity of hepatic necrosis and reflect attempts to resolve inflammation during AALF. It is the excessive production of these mediators that "spill-over" and increase the risk of systemic sepsis. We sought to delineate hepatic and systemic cytokine responses in experimental and human AALF, and, determine whether there is production of anti-inflammatory cytokines in the liver which "spill-over" into the systemic circulatory compartment. Aim: We sought to delineate hepatic and systemic inflammatory responses in experimental and human AALF, and, determine whether there is a "spill-over" of hepatic anti-inflammatory mediators into the systemic, circulatory, compartment. Method: Median levels (pg/ml) of hepatic IL-1ß, IL-4, -6, -10, -12, -17, IFN-Y, MCP-1, TNF-α, TGF-ß1 were measured using proteome arrays in 10 human AALF explants and 8 normal control liver tissue samples. Hepatic and serum levels of IL-1ß, IL-4, -6, -10, -12, -17, MCP-1, TNF-α, TGF-ß1 were measured in 200mg/kg i.p. APAP treated male C3H/HeH mice (n=5 severe necrosis, n=5 moderate necrosis) and 5 control mice. Regional levels (portal vein (PV)), hepatic vein (HV), arterial (art)) of TNF-α, IL-10 were determined using ELISA in 3 AALF patients at time of liver transplantation. Results: In human AALF, hepatic levels of IL-6 (115 vs 75; p=0.02), IL-10 (1.8 vs 0.6; p=0.03), TGF-ß1 (3009 vs 1323; p<0.0001) were elevated in AALF compared to controls while IL-1ß, IL-12, IL-17, IFN-Y and TNF-α were unchanged. Higher hepatic levels of IL-4 (37 vs 25; p<0.01), IL-10 (90 vs 66; p<0.01), IL-12 (11 vs 7.8; p<0.01) and TGF-ß1 (2521 vs 540; p<0.01) were detected in mice with severe hepatic necrosis compared to those with moderate necrosis and normal controls. Similar to human AALF, serum pro- (IL-6 (146 vs 13; p<0.01), IL-1ß (104 vs 62 (p=0.07)) and anti-inflammatory cytokines (IL-4 (3 vs 0.8; p<0.01), IL-10 (47 vs 1; p<0.01) were elevated compared to normal controls during murine AALF. Conclusion: We demonstrate a hepatic inflammatory microenvironment favouring resolution of inflammation/tissue repair processes. In vivo hepatic production and systemic "spill-over" of the immunosupressive cytokines is observed and may account for functional monocyte deactivation and the marked predisposition to sepsis in AALF. The marked similarities in anti-inflammatory mediator profiles between human and murine models of AALF provide a rationale on which to base the studies examining evolution of disease and development of immunomodulatory strategies to ameliorate acute liver injury and promote tissue repair.